Шли с базара индюки: [Потешки] / Виктор Хесин ; [худ. В. А. Жигарев] - Хесин Виктор (Потешки для малышей, 2007)
Экземпляры: с/ф № 8 (20140424) / Инвентарный номер: 43317 / Цена: / Сис.шифр: 84Р7 / Авт.знак: Х 40 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6